STRATEGY MODELLING FOR AN ISSUER OF STRUCTURED BONDS : Fair Value, Marketing and Hedging - Karimov, Arslan (My University, 2023)
This study aims to contribute to the existing literature on structured products by exploring the engineering and issue process, providing a comprehensive literature review and a new classification approach, investigating various pricing methodologies, and providing new pricing methods. This study provides a new classification approach to structured products incorporating the existing approaches and contributing by adding new aspects such as the features or special conditions within the structured products. The research incorporates various pricing approaches that were either implemented alone or in a com-bination with other methods, including Black-Scholes model, Lattice models, Monte Carlo simulation, finite differences methods, bootstrapping and time-series models. Empirical results reveal that there is a significant difference between the resulting estimated intrin-sic value of a structured product, moreover some of the methods could not be imple-mented in any way. Additionally, the study shows that certain types of publicly available structured products listed are overpriced by the market. Finally, the study provides an experiment carried out by implementing one of the incorporated approaches and models the issue of a Derivative Warrant.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance